The Cultural Tourism of the French - Barbier, Bernard (Turyzm/Tourism, 2005)
This paper presents motives, organizers and destinations of cultural tourism in France. The author has stressed the influence of education and national traditions on development of cultural tourism in this country. The paper provides characteristics of main French tour-operators dealing with this type of tourism. It also analyses to what extent different regions and continents are covered with published guidebooks and discusses what are destinations preferred by the French cultural tourists.